Dynamics and Mechanism of Flame Retardants in Polymer Matrixes: Experiment and Simulation - Yoon, Donghwan; Jung, Hyun Tae; Kwon, Gyemin; Yoon, Yeoeun; Lee, Minsoo; Bae, Imhyuck; Joo, Beom Jun; Kim, Mansuk; Lee, Sun Ae; Lee, Jihye; Lee, Yeonhee; Cho, Eunseog; et al. (AMER CHEMICAL SOC, 2013)
We investigate the dynamics and the mechanism of flame retardants in polycarbonate matrixes to explore for a way of designing efficient and environment-friendly flame retardants. The high phosphorus content of organic phosphates has been considered as a requirement for efficient flame retardants. We show, however, that one can enhance the efficiency of flame retardants even with a relatively low phosphorus content by tuning the dynamics and the intermolecular interactions of flame retardants. This would enable one to design bulkier flame retardants that should be less volatile and less harmful in indoor environments. UL94 flammability tests indicate that even though the phosphorus content of 2,4-di-tert-butylphenyl diphenyl phosphate (DDP) is much smaller with two bulky tertiary butyl groups than that of triphenyl phosphate (TPP), DDP should be as efficient of a flame retardant as TPP, which is a widely used flame retardant. On the other hand, the 2-tert-butylphenyl diphenyl phosphate (2-tBuDP), with a lower phosphorus content than TPP but with a greater phosphorus content than DDP, is less efficient as a flame retardant than both DDP and TPP. Dynamic secondary ion mass spectrometry and molecular dynamics simulations reveal that the diffusion of DDP is slower by an order of magnitude at low temperature than that of TPP but becomes comparable to that of TPP at the ignition temperature. This implies that DDP should be much less volatile than TPP at low temperature, which is confirmed by thermogravimetric analysis. We also find from Fourier transform infrared spectroscopy that Fries rearrangement and char formation are suppressed more by DDP than by TPP. The low volatility and the suppressed char formation of DDP suggest that the enhanced flame retardancy of DDP should be attributed to its slow diffusivity at room temperature and yet sufficiently high diffusivity at high temperature.
Keywords: RESORCINOL BIS(DIPHENYL PHOSPHATE); COMPASS FORCE-FIELD; TRIPHENYL PHOSPHATE; THERMAL-DEGRADATION; AB-INITIO; PLASTICIZERS; SURFACE; PARAMETERIZATION; VALIDATION; AIR